Collective market-making efforts at an engineering conference - Guido Möllering (Max Planck Institute for the Study of Societies, 2010)
This paper advances research on institutional work in market constitution processes. I show how purposive, coordinated action is organized under conditions of uncertainty through practices of rendering irreducible uncertainty tolerable. Building on recent developments in institutional theories of organization, market sociology, and the concept of field-configuring events, I analyze collective market-making efforts at a conference on the next generation of lithography technology for manufacturing semiconductors. I use original documents and 76 field interviews in a qualitative analysis to identify and understand the main practices of collective institutional work at the conference, along with the immediate consequences of these practices. My findings show that the overall purpose of the conference was to generate momentum toward commercialization, in spite of remaining uncertainty, through practices of bootstrapping, roadmapping, leader-picking, and issue-bracketing. These are practices of ignoring, denying, displacing, and suspending uncertainty, respectively. I contribute important clarifications of the meaning of purposive action and agency in institutional work and I advance actiontheoretical explanations of market constitution processes by identifying activities involved in shaping a market that is still in the making. – – Diese Studie trägt zur Erforschung von Institutional Work in Marktkonstitutionsprozessen bei. Ich zeige, wie gezieltes, koordiniertes Handeln unter Ungewissheit durch Praktiken organisiert wird, die die Ungewissheit tolerierbar machen. Ausgehend von den jüngsten Erkenntnissen der institutionalistischen Organisationstheorien, der Marktsoziologie und dem Begriff des Field-Configuring Events analysiere ich kollektive Bemühungen der Markterschaffung bei einer Konferenz über die nächste Generation von Lithographietechnologie für die Halbleiterproduktion (Next Generation Lithography). Anhand von Originaldokumenten aus dem Feld sowie 76 Interviews führe ich eine qualitative Analyse durch, mit der die wichtigsten Praktiken des kollektiven Institutional Work bei der Konferenz und deren unmittelbare Folgen identifiziert und verstanden werden können. Meine Ergebnisse zeigen, dass es in der Konferenz vor allem darum ging, einen gewissen Schwung, das heißt: eine zielgerichtete Kraft zu erzeugen, die die Kommerzialisierung einer neuen Technologie anstoßen soll - und zwar trotz der verbleibenden Ungewissheit. Dies wurde durch Praktiken des Ignorierens, Leugnens, Verschiebens und Aufhebens von Ungewissheit erreicht, die ich mit den englischen Begriffen bootstrapping, roadmapping, leader-picking und issue-bracketing genauer bezeichne. Die Studie trägt zur weiteren Klärung der Bedeutung von gezieltem Handeln und der Rolle von Akteuren in Institutionalisierungsprozessen bei. Ich bringe handlungstheoretische Begründungen von Marktkonstitutionsprozessen voran, indem ich Praktiken beschreibe, die einen Markt beeinflussen, der sich noch im Entstehungsprozess befindet.
Keywords: 300; Halbleiterindustrie; Fertigungstechnik; Marktveranstaltung; Konferenz; Verhalten; Soziale Beziehungen; Institutionalismus